واقع سوق إعادة التأمين في الجزائر-دراسة تحليلية للفترة (2010-2018) The reality of Algeria's reinsurance market- an analytical study between 2010-2018 - علمي, حسيبة; بهلولي, فيصل (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
تهدف هذه الدراسة إلى تحليل واقع سوق إعادة التأمين في الجزائر من خلال دراسة جانبي إعادة التأمين، جانب التنازل عن الأقساط المصدرة من قبل شركات التأمين الجزائرية، وجانب القبول من قبل الشركة المركزية لإعادة التأمين. توصلنا إلى عدة نتائج منها أن متوسط الأقساط المتنازل عنها في شركات التأمين الجزائرية يقدر بـ30% من إجمالي الأقساط المصدرة خلال فترة 2010-2018، حيث أن 60% منها توجه للسوق المحلي لإعادة التأمين، وبدورها الشركة المركزية لإعادة التأمين تسند 40% من الأقساط المقبولة للسوق الدولي لإعادة التأمين، بالمقابل تحملت هذه الأخيرة (CCR) ما نسبته فقط 11.82% من إجمالي التعويضات المدفوعة خلال نفس الفترة. The aim of this study is to analyze the reality of Algeria’s reinsurance market, based on the two main aspects of reinsurance. The first aspect is the cession of premiums by Algerian insurance companies, and the second aspect is accepting the CCR. Many results were concluded, the most important being that the Algerian insurance companies' cession rate is 30% of the gross written premiums between 2010-2018, while 60% of the cessions are for the national reinsurance market, and finally, the CCR retrocede 40% of the accepted premiums to the international reinsurance market, which in return incurred 11.82% of gross claims paid during the same period